2011
DOI: 10.1007/s10461-011-0037-5
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting Substance-Using Men Who Have Sex With Men into HIV Prevention Research: Current Status and Future Directions

Abstract: Research investigators have identified increasing challenges to the recruitment of men who have sex with men (MSM) for observational and intervention HIV/AIDS studies. To address these issues, program staff from the National Institute on Drug Abuse convened a meeting on April 28th to 29th, 2009 to discuss issues in MSM recruitment. The panel indicated that there was decreased community identification with HIV research, although altruistic, community-oriented motives continued to be important. Substance use add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…For example, among IDUs, relationships are sometimes characterized as multiplex (e.g., network contacts may be drug use partners, sex partners, and/or social companions) and/or transactional (e.g., exchange of sex or drug for money, food, or shelter), which may provide a more fertile environment for the social influence and social exchange on which RDS-based recruitment depends. 18 The recruitment patterns and structure of recruitment chains also reflect problematic dynamics for RDS-based recruitment in this population. Among the 55 referral chains linked to productive seeds, the majority (52 %) had only one recruitment wave, and only 18 % had had lengths of four waves or more.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…For example, among IDUs, relationships are sometimes characterized as multiplex (e.g., network contacts may be drug use partners, sex partners, and/or social companions) and/or transactional (e.g., exchange of sex or drug for money, food, or shelter), which may provide a more fertile environment for the social influence and social exchange on which RDS-based recruitment depends. 18 The recruitment patterns and structure of recruitment chains also reflect problematic dynamics for RDS-based recruitment in this population. Among the 55 referral chains linked to productive seeds, the majority (52 %) had only one recruitment wave, and only 18 % had had lengths of four waves or more.…”
Section: Discussionmentioning
confidence: 98%
“…Small network size could be due to variation in sexual minority identity development in this age group 30 as well as the relatively narrow age range for eligibility (i.e., 16-20 years old). Others have suggested that different research participation payment structures are needed to incentivize YMSM in particular, 18 given low rates of participation. An alternative system was developed for adult MSM (e.g., raffle with large cash prize) in an RDSbased study; 31 however, any increase in incentive payments would need to be balanced with concerns about undue influence and/or coercion, 1 particularly for 20 these violate the RDS assumption of random recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A modified form of respondent driven sampling 17 was used to recruit participants. Following recommendations outlined by Jenkins 18 , a larger initial convenience sample of “seeds” ( N = 172; 38.2%) was utilized due to difficulties maintaining referral chains in the small social networks of YMSM compared to other populations (e.g., injection drug users). This approach has been used successfully in previous research with YMSM 19,20 .…”
Section: Methodsmentioning
confidence: 99%